Régimen legal especial de salud de las Fuerzas Militares frente a los derechos de los trabajadores civiles del Ministerio de Defensa y Fuerzas Militares en Colombia regidos por el decreto 1214 de 1990 (2019)
The labor rights of civilian workers of the Ministry of Defense and military forces in Colombia have been affected by new laws that eliminated benefits that they had before, for this reason they go to the jurisdiction to be recognized again under the principle of favorability whenever their working conditions deteriorated, as well as the Political Constitution of Colombia enshrines in Article 53, some guiding principles of labor law and also the substantive code of work, workers demand they be respected and applied. The State as protector must guarantee the labor stability of the workers as well as the rewards they receive that can not be diminished because it goes against Constitutional principles, when they are eliminated some of their labor benefits directly influences the quality of life of the workers. the people and their families who also depend economically on that income that the worker receives.